A Man with Unilateral Endophthalmitis: A Case of Disseminated Nocardiosis. (23rd March 2015) - Navarrete-Navarrete, N.; Escobar Sevilla, J.; Toribio García, M.; Urbano, F.; Sabio, J. M.; Jiménez-Alonso, J.
Abstract : We present the case of a patient with an infection by Nocardia which manifested itself with monocular endophthalmitis. Nocardia infection is not common and ocular involvement is one of the most uncommon presentations. In these cases it is very important to make an early diagnosis and intensive treatment to prevent the visual prognosis.